PEMANFAATAN LIMBAH CANGKANG KERANG BULU SEBAGAI ADSORBEN UNTUK MENJERAP LOGAM KADMIUM (II) DAN TIMBAL (II) - Akhmad Anugerah S, Iriany (Jurnal Teknik Kimia USU, 2015)
Adsorbent from fur shells could be used to adsorb heavy metal ions such, as Cd (II) and Pb (II). This is shown by the research of adsorption using the fur shells. This research was aimed to characterize the fur shells. Variables in this research were the activation temperature and concentration of the metal solution. This research was begun with reduction of the shell size to 140  mesh, then thermal activation at temperature 110ᴼC, 500ᴼC and 800ᴼC in the furnace. After that adsorbent was characterized using BET, measured its density, moisture content and ash, the adsorption capacity of the adsorbent was tested by using solution of Cd (II) and Pb (II), and then the concentration of the remaining solution was measured by AAS. The result showed that activated adsorbent  at temperatures 110ᴼC, 500ᴼC and 800ᴼC had surface area of 725.43; 807.94; and 803.822 m2/g. Density was inversely proportional to the activation temperature, the value of moisture content and ash obtained were in accordance to SNI. Activated adsorbent at 500ᴼC suitabled with  the Freundlich Isotherm.